In her father’s image: reflections on my dramaturgy of the play School of Wives - Golub, Dora (Molière u hrvatskoj kulturi, 2024)
This essay is conceived as a sketch of the dramaturgical concept, as well as a critical reflection of the work on the play School for Wives by Molière in the production of the Croatian National Theatre in Osijek in 2020, in which the author of the article was involved in the function of dramaturge. It also functions as an analytical training ground for the elaboration of the thesis about the possibilities of (re)writing feminist script around the dominant narrative given by the canonical play. The text breaks down the conceptual settings of the dramaturgical structure of the performance in two parts: in the first part, it is mainly focused on the explanation of establishing the main character’s perspective as the dominant one in the production of meaning, with regard to representational mechanisms that deny stage realism and, in metatheatrical key, create the appearance of a conspiracy around the protagonist. The principle of theatrical deconstruction is also clarified: it materializes in performance by reconfigurations of stage frames, variable in size, the starting point of which rests on the idea of well-known portrait vignettes on the level of language, which Molière frequently used as a rhetorical strategy in his comedic practice. The second part of the article is primarily focused on the critical and satirical positioning of the performance to the character of Arnolphe as the bearer of the triple role of father, tutor, and future husband of his ward. In his character and actions, the writer finds parallelisms, but also deviations from the libertine philosophy represented in French literature of the 17th and particularly 18th century, ultimately politically positioning the ambivalent protagonist of the comedy as a conservative. Finally, the paper reconstructs the stage realization of Arnolphe’s narcissistic mirroring in the vein of Pygmalion, which lead to a change in the ending set by original, and thus to a genre shift of the performance in favor of tragedy.